2018
DOI: 10.1371/journal.pone.0196683
|View full text |Cite|
|
Sign up to set email alerts
|

Infant CPAP for low-income countries: An experimental comparison of standard bubble CPAP and the Pumani system

Abstract: IntroductionAccess to inexpensive respiratory support to newborn infants improves survival in low-income countries. Standard bubble continuous positive airway pressure (CPAP) has been extensively used worldwide for more than 30 years. One project aimed at providing affordable CPAP is the Pumani system developed by Rice 360°. Compared to standard bubble CPAP the system has an unconventional design. The aim was to compare the Pumani system with two traditional bubble CPAP systems, focusing on in-vitro performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…The increased tubing resistance also leads to increased resistance to breathing (figure 3). This is expected and has been shown for other systems that generate CPAP using outflow resistance 29 30…”
Section: Discussionsupporting
confidence: 64%
“…The increased tubing resistance also leads to increased resistance to breathing (figure 3). This is expected and has been shown for other systems that generate CPAP using outflow resistance 29 30…”
Section: Discussionsupporting
confidence: 64%
“…A 2002 Cochrane review showed that CPAP in spontaneously breathing preterm infants with respiratory distress syndrome reduced mortality by 48% [ 5 ]. Bubble CPAP (bCPAP) is one of several methods of CPAP generation that has been in use worldwide for more than 30 years [ 6 ]. It is safer than mechanical ventilation [ 7 ], simple to operate [ 8 ] and the commercial model is about one- tenth the cost of mechanical ventilators [ 9 ].…”
Section: Project Evaluationmentioning
confidence: 99%
“…It is safer than mechanical ventilation [ 7 ], simple to operate [ 8 ] and the commercial model is about one- tenth the cost of mechanical ventilators [ 9 ]. These factors make bCPAP an excellent candidate for use in LMICs [ 6 ].…”
Section: Project Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplicity of bubble CPAP, combined with reports of favourable outcomes from centres with experience in its use, has long generated interest in this form of CPAP. There have been a number of trials comparing bubble CPAP with other CPAP forms but with heterogeneity in reported outcomes 9–16. In one recent systematic review, bubble CPAP was shown to be safe and reduced the need for mechanical ventilation, but only studies from low-income and middle-income countries were included 17.…”
Section: Introductionmentioning
confidence: 99%